Legal Regulation of Social Security New Benefits Introduced In the Retirement and Social Security Law No. (18) Of 2023 - Saba Noman Rasheed (Journal of Legal Sciences, 2024)
The importance of the rules governing Social Security for the children of the community and the organization expands in the Social Security Law, which is formulated according to intellectual variables social policy. By the nature of this international law, which is generally proven in most countries of the world, including Iraq, and according to the general variables that have raced to influence the Iraqi society, it is necessary to recognize the positive points in the pension and Social Security Law. Which abolished the law and the stability of the calculation rules for all financial rights, and otherwise includes all the requirements of security and not limited to the concept of (social insurance) by regulating the established legal rules cultural rights (such as cultural workers ’ clubs) and Housing Rights (by regulating the right of a worker in housing projects in established cities exclusively for workers) In its time, Iraq counted the most developed law, but the breakthrough in the field of achieving (social security) for the category of workers in the seventies of the last century among the countries of the region, and (with the issuance of the Constitution of 2005, the law no longer corresponds to the basic norm in society) also, Iraq’s accession to the agreements requires fulfilling its obligations to the international community and the International Labor Organization ILO, not to mention the changes in the Iraqi labor market influenced by all the influencing factors and its close connection with the labor law, which was changed by the issuance of a law (37) for the year 2015, which means the passage of three labor laws over the law on retirement security in force and the transformation of each of them into a different specific economic thought About the other. The Retirement and Social Security Law No. 18 of 2023 has added new branches that were not addressed or addressed in previous security legislation, but in line with all the global social and economic changes and recent trends that are prominent in most societies, it is necessary to find legislative treatment for two important branches, namely the guarantee of workers if they are unemployed, and the so-called Optional membership of the guarantee.